Canonical WNT/β-Catenin Signaling Activated by WNT9b and RSPO2 Cooperation Regulates Facial Morphogenesis in Mice - Jin, Yong-Ri; Han, Xiang Hua; Nishimori, Katsuhiko; Ben-Avraham, Dan; Oh, Youn Jeong; Shim, Jae-won; Yoon, Jeong Kyo (Frontiers in Cell and Developmental Biology, 2020)
The R-spondin (RSPO) family of proteins potentiate canonical WNT/β-catenin signaling and may provide a mechanism to fine-tune the strength of canonical WNT signaling. Although several in vitro studies have clearly demonstrated the potentiation of canonical WNT signaling by RSPOs, whether this potentiation actually occurs in normal development and tissue function in vivo still remains poorly understood. Here, we provide clear evidence of the potentiation of canonical WNT signaling by RSPO during mouse facial development by analyzing compound Wnt9b and Rspo2 gene knockout mice and utilizing ex vivo facial explants. Wnt9b;Rspo2 double mutant mice display facial defects and dysregulated gene expression pattern that are significantly more severe and different than those of Wnt9b or Rspo2 null mutant mice. Furthermore, we found the suggestive evidence that the LGR4/5/6 family of the RSPO receptors may play less critical roles in WNT9b:RSPO2 cooperation. Our results suggest that RSPO-induced cooperation is a key mechanism for fine-tuning canonical WNT/β-catenin signaling in mouse facial development.